The Relationship between Alexithymia and Emotional Maturity with the Mediation of Attachment Styles in Cardiovascular Patients - Mina Rostami; Morteza Soleimani; Mahsa Abbasi; Alireza Sadeghi; Vahid Toupchi Khosroshahi; Pooya Davasaz Rabbani; Parinaz Sadat Amiri Sararoodi (مجله علوم پزشکی صدرا, 2024)
Introduction: Psychological factors might play a role in the onset and exacerbation of cardiovascular disease. This study aimed to determine the relationship between Alexithymia and Emotional Maturity with the mediation of Attachment Styles among cardiovascular patients in Zanjan, Iran.Methods: The present study has a descriptive-correlational design. The statistical population of this study encompassed a range of 670 patients with cardiovascular diseases who were referred to the Cardiology Clinic of Ayatollah Mousavi Hospital in Zanjan from March and August 2019. The sample size was estimated to be 244 people using Cochran formula. Data collection tools included Hazen and Shaver’s standard adult attachment style questionnaire, Toronto’s ataxia, and Singh and Bhargava questionnaires. The Pearson correlation coefficient and multiple regression analyses were done using SPSS 24 software.Results: There was a positive correlation between alexithymia with emotional instability (r=0.14, P<0.01), personality decay (r=0.36, P<0.01), and emotional maturity (r=0.38, P<0.01). The results of multiple regression analysis showed that emotional instability (P=0.009), personality decay (P=0.016), and emotional immaturity (P=0.009) significantly predicted secure style. Additionally, difficulty in describing emotions significantly predicted avoidant style (P=0.034). Emotional maturity (P=0.006) and difficulty recognizing emotions (P=0.009) also significantly predicted ambivalent style.Conclusion: Personality traits and emotional alexithymia can be used as indicators for predicting attachment styles and social behaviors, and specifically, lack of emotional stability, personality disintegration, and emotional alexithymia can predict secure and ambivalent styles to some extent. Also, difficulty in describing emotions and emotional immaturity have the ability to predict the avoidant style. These results can help to better understand individual behaviors and design solutions to improve behavior.